Study of Traditional Village Arrangement in Rote Ndao District - MESSAKH, Hendrikhsan A.B.; DJAHA, Ajis Salim Adang; TODA, Hendrik (Journal of Tourism Economics and Policy, 2023)
The regulation regarding the designation of customary villages is a form of formal juridical recognition by the government of the existence and rights of indigenous peoples who are spread throughout Indonesia, especially in Rote Ndao District. This research is a qualitative descriptive study with primary and secondary data sources collected through qualitative observation, qualitative interviews, qualitative documents search and qualitative audio and visual materials. ) then the data that has been collected is analyzed using the data analysis steps proposed by Miles, Huberman and Saldana (2014: 14) The results of the study found that the structuring of villages into traditional villages in Rote Ndao Regency does not fulfill several elements, namely; (a) customary territories and customary assets no longer function according to community development, (b) customary government institutions, solidarity of indigenous peoples and instruments of customary law norms that still exist and do not conflict with applicable laws and regulations, (c) solidarity indigenous peoples and instruments of customary law norms that still exist and do not threaten the sovereignty and integrity of the state and (d) customary territories, solidarity of indigenous peoples, customary government institutions, customary assets and instruments of customary law norms have partially disappeared and have not been recognized by the state while the inhibiting factors in village management, especially changing the status of a village to a traditional village in Rote Ndao Regency, namely; (a) bad policies and (b) the will of regional heads.